Dimensions of The Islamic Law and Human Rights in The Protection of Children from Convicted Parents - Zuhriah, Erfaniah; Fuadi, Suud; Sukadi, Imam; Ashari, Zahrah Salsabillah (De Jure: Jurnal Hukum dan Syari'ah, 2024)
Protection for children separated from their parents, particularly due to parental incarceration, is a pressing issue in Indonesia that demands serious attention. The absence of parental support and guidance places these children in vulnerable situations, negatively impacting their physical, emotional, and social well-being. This study examines the importance of legal and social protection for these children and explores the role of the state and government in providing adequate protection and welfare guarantees. Previous research reveals gaps in integrating Islamic legal principles with child protection policies that are contextual and relevant to contemporary social challenges. This article presents a review of key Islamic legal concepts related to child protection, such as maslahah mursalah, and integrates them with international human rights standards, such as the Convention on the Rights of the Child (CRC). Employing an empirical approach, the study investigates the implementation and practical outcomes of child protection laws. Primary data were gathered through interviews and observations involving key stakeholders, complemented by secondary data from books, journal articles, and legislative documents, including the Child Protection Act. The findings reveal that children separated from incarcerated parents often face neglect, discrimination, and social vulnerability. A case study of the Women’s Prison Class II A in Malang City highlights inadequate child protection measures due to insufficient government funding, which hampers the effective delivery of developmental and protective services for these children. To address these challenges, stronger regulatory frameworks and increased budgetary support are essential. Enhancing the role of the state in implementing robust policies will not only ensure the welfare of affected children but also set a standard for societal participation in fostering healthy, discrimination-free environments. Such measures are critical for safeguarding the rights and development of these vulnerable children.